Risk Planning – um jogo educativo para auxiliar no ensino de gerenciamento de riscos em projetos de software - Santos, Ana Paula da Silva dos (2017)
Risk management in software projects is an area of extreme importance to the success of the project. It is essentially about looking at a situation and making the best decisions to work around or deal with a threat or opportunity. However, the acquisition of the skills and capabilities to make such decisions and to be able to understand the impact involved are subjective aspects, linked to the experience, in this way it becomes difficult to train in the classroom just studying the theory. Educational games can be used as an effective tool in the teaching and learning process, since they amuse and motivate at the same time, facilitating learning and increasing the retention capacity of what has been taught. They provide a mechanism for putting into practice what is being studied in the classroom, facilitating learning and connecting theory to practice. Given this context, the present work presents an educational game of risk management in software projects. The proposed game is called Risk Planning. The game simulates a risk management process in a simulated environment in which the player has to identify, analyze and treat the risks of a software project. The results obtained with the game Risk Planning were satisfactory. It showed up to be a fun and easy game to be learned throughout the rounds. The fact that players are divided into teams and the game has a system of losses and gains, generates a fun environment that encourages healthy competition among players, making them more committed to properly manage the risks of their project so that can win the game.